ANALISIS PENGUKURAN KINERJA REKSA DANA SAHAM DENGAN METODE RISK-ADJUSTED RETURN DI BURSA EFEK INDONESIAPERIODE TAHUN 2011-2013 - Datu Pinastiko Adi; Musaroh Musaroh Musaroh (JURNAL ILMU MANAJEMEN, 2014)
This study aimed to investigate the performances of the equity funds based on Risk-Adjusted Return using Sharpe, Treynor, Jensen, M^2and Information Ratio methods along with comparison between the performances of the equity funds and benchmark performance in research periods. The data analysis methods were Sharpe, Treynor, Jensen, M^2and Information Ratio methods. The data analysis using Sharpe and Treynor methods produced the same results; In 2011 there are 20 equity funds with positive performances. In 2012 there are 42 equity funds with positive performance, and in 2013 6 equity funds with positive performance. According to Jensen method, in 2011 there are 19 equity funds with positive performance. In 2012 there are 12 equity funds with positive performances. Meanwhile, in 2013 19 equity funds with positive performance. According to M^2 method, in 2011 there are 19 equity funds with positive performance. In 2012 there are 12 equiy funds with positive perfomance. Meanwhile, in 2013 23 equity funds with positive performance. According to Information Ratio method, in 2011 there are 19 equity funds with positive performance. In 2012 there are 12 equity funds with positive performance. Meanwhile, in 2013 19 equity funds with positive performance. The results of the comparison between the performances of the equity funds to benchmark show that in 2011, 18 equity funds had performances above the benchmark performance (outperform), in 2012, 13 equity funds had performances above the benchmark performance (outperform). Meanwhile, in 2013 there are 16 equity funds had performance above the benchmark performance (outperform).